Increased expression of EZH2, a polycomb group protein, in bladder carcinoma - Arısan, Serdar; Ünsal, Zeynep Narçin; Çaşkurlu, Turhan; Çakır, Ömer Onur; Ergenekon, Erbil; ARISAN, ELİF DAMLA (My University, 2005)
Introduction: Recent experiments have demonstrated that polycomb group gene enhancer zeste homolog 2 (EZH2) is highly expressed in many cancer types. Therefore, we aim to demonstrate EZH2 gene expression in transitional cell bladder cancer. Patients and Methods: The reverse transcriptase-polymerase chain reaction (RT-PCR) was used for detection of EZH2 mRNA levels in healthy and cancerous human bladder specimens. Also, expression of the particular protein was determined by Western blotting and immunohistochemistry to confirm RT-PCR results. Results: Gradually increased expression of EZH2 was detected by mRNA and protein levels in highly advanced bladder cancer specimens. In contrast, 100% of control subjects were negative for EZH2 expression. The expression of EZH2 was more frequent in G3 (92%) than G1-G2 (62–63%) and more frequent in T1-2 (72–85%) than Ta (56%). Western blot analysis results confirm the RT-PCR results. Conclusions: EZH2 overexpression precedes high frequencies of proliferation and the gradual advance of bladder cancer. These observations suggest that deregulated expression of EZH2 is associated with bladder carcinoma.
Keywords: EZH2 gene expression; Enhancer zeste homolog 2; EZH2, polycomb group protein; RT-PCR; Bladder